Rancangan Receiver Automatic Dependent Surveillance Broadcast menggunakan Flightware Prostick Plus dan Rasperry PI di Politeknik Penerangan Makassar - Rusman; Sasongko (Politeknik Penerbangan Makassar, 2022)
Automatic Dependent Surveillance-Broadcast (ADS-B) is a surveillance technology using positional information from broadcast satellites continuously. The problem that is also faced at Indonesian airports is the limited surveillance equipment available at each airport, especially ADS-B equipment, where the average branch and unit airports in Indonesia do not yet have ADS-B equipment. So the formulation of the problem that the author raises from this research is how to design a Receiver Automatic Dependent Surveillance-Broadcast (ADS-B) tool using FlightAware ProStick Plus and Raspberry Pi. Tool design consists of tool design and how the tool works then include hardware and software components used for aircraft detection. The results of this study indicate that the ADS-B Receiver is made to detect aircraft in real-time in the coverage area of ​​the ADS-B Receiver and the results obtained from running the ADS-B Receiver are in the form of display maps that can show where the aircraft is located to the ADS-B Receiver.